Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1088/1361-6668/ac8025
|View full text |Cite
|
Sign up to set email alerts
|

K-doped Ba122 epitaxial thin film on MgO substrate by buffer engineering

Abstract: Molecular beam epitaxy of K-doped Ba122 (Ba1−x K x Fe2As2) superconductor was realized on an MgO substrate. Microstructural observation revealed that the undoped Ba122 served as a perfect buffer layer for epitaxial growth of the K-doped Ba122. The film exhibited a high critical temperature of 39.8 K and a high critical current density of 3.9 MA/cm2 at 4 K. The successful growth of epitaxial thin film will enable artificial single grain boundary on oxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Although two phases are clearly visible in the out-of-plane scans, they are hard to recognize in inplane scans due to the small difference in the lattice parameter a (figures 10(c) and (d)). The 103 ϕ-scan confirmed that Kdoped Ba122 grew epitaxially on Ba122-buffered MgO [24].…”
Section: Growth Methodsmentioning
confidence: 75%
See 1 more Smart Citation
“…Although two phases are clearly visible in the out-of-plane scans, they are hard to recognize in inplane scans due to the small difference in the lattice parameter a (figures 10(c) and (d)). The 103 ϕ-scan confirmed that Kdoped Ba122 grew epitaxially on Ba122-buffered MgO [24].…”
Section: Growth Methodsmentioning
confidence: 75%
“…Once the high angle grain boundaries are eliminated, such broadening is absent: figures 15(c) and (d) show the temperature dependence of the resistance for the K-doped Ba122 epitaxial film grown on Ba122-buffered MgO. The film showed a high T c,90 of 39.2 K with a small transition width of 1.7 K. The high T c value is ascribed to the strain effect [24]. The presence of high angle grain boundaries also reduces J c significantly (figure 16(c)).…”
Section: Physical Properties Of Ba 1−x Kxfe 2 As 2 Grown On Mgomentioning
confidence: 99%
“…The seed layer also allows for the extension of the temperature window for optimal growth down to 200 °C. Even if the seed layer growth conditions lead to off-stoichiometry Fe(Se,Te) film due to Te loss in the film at high temperature 33 it provides an ideal template for Fe(Se,Te) because the seed allows for homoepitaxial growth of the superconducting layer 32 , 34 , 35 , However, its actual role still has to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…7) A high critical current density J c has been seen in many single-crystal and thin-film studies, demonstrating that high vortex pinning is possible in the Ba122 system. [9][10][11][12][13][14][15][16] Foreseeing practical applications, the most versatile form is a long-length wire in which the materials are inevitably polycrystalline; thus J c across the grain boundary (GB) network, the so-called intergrain J c , becomes the very important factor. 17,18) There are both intrinsic and extrinsic GB current-blocking mechanisms in FBS.…”
mentioning
confidence: 99%